Kerangka Konseptual Asesmen Menulis Teks Argumentasi: Desain Rubrik Analitik Berbasis Literasi AI - Ayu Herawati; Sudiati Sudiati; Esti Swatika Sari (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The integration of Generative Artificial Intelligence (GenAI) in language education demands a fundamental redefinition of the construct of writing assessment. A major challenge currently is the inability of conventional rubrics—which emphasize mechanical accuracy and surface structure—to distinguish between students' cognitive competence and algorithmic sophistication. This article aims to develop a conceptual framework and prototype design of a new analytical rubric for the assessment of argumentative texts that explicitly integrates the AI ​​literacy dimension. Using a conceptual study method, this research synthesizes key references including language assessment theory, the Toulmin argumentation model, and the concept of distributed agency. This research proposes a paradigm shift in assessment from product-oriented to process-oriented through a